Implications of palm-based biodiesel blend mandate on the biodiesel industry growth in Malaysia: evidence from causal loop diagram - Zabid, M. Faeid M.; Zainal Abidin, Norhaslinda; Applanaidu, Shri Dewi (Faculty Economics & Administration, University of Malaya, 2018)
The government’s recent announcement to increase blend mandate of B10 for transportation sector and B7 for industrial sector is being welcomed by experts as a huge turning point for Malaysia palm-based biodiesel industry. However, concerns remain on the viability of the industry, especially during low crude oil price period. The main aim of this paper is to assess the impact of various blend mandates on Malaysia’s biodiesel industry based on cost-profit, environmental, and wide economic perspectives. This research employs the causal loop diagram of system dynamics method which explains how things change through time and how actions and reactions cause and influence each other. The findings indicate the government’s effort is rational and has a positive impact on the environment and economy but a negative impact from the cost-profit perspective. The study results allow policy makers such as MPOB to understand and to predict how various blend mandate might affect not only the biodiesel industry in the long term but also the cost-profit, environmental and other economic variables.